2006
DOI: 10.1063/1.2425036
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-free growth of uniform ZnO nanowire arrays on prepatterned substrate

Abstract: Uniform and ordered ZnO nanowire arrays have been fabricated on the nanopatterned SiO2∕GaN substrate without metal catalysts using hydrothermal synthesis. The nanopatterns on SiO2∕GaN substrate with an average diameter of 65nm are produced by inductively coupled plasma etching using anodic alumina template as a mask, which provides nucleation sites for the vertical ZnO nanowires growth. High quality of the aligned uniform ZnO nanowire arrays grown on GaN substrate was confirmed by x-ray diffraction, transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
1
14
1
Order By: Relevance
“…The resonant Raman spectra of all the samples show multiphonon LO modes up to fourth order. It has been reported that the number of multiphonon scattering process observed in semiconductors varies monotonically with polaron coupling coefficient, and for ZnO with a large value of polaron coupling coefficient, LO phonons up to 10th order is expected [7]. The observation of multiphonon resonant Raman peaks in ZnO nanorods further justified the good optical quality of ZnO products.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…The resonant Raman spectra of all the samples show multiphonon LO modes up to fourth order. It has been reported that the number of multiphonon scattering process observed in semiconductors varies monotonically with polaron coupling coefficient, and for ZnO with a large value of polaron coupling coefficient, LO phonons up to 10th order is expected [7]. The observation of multiphonon resonant Raman peaks in ZnO nanorods further justified the good optical quality of ZnO products.…”
Section: Resultsmentioning
confidence: 75%
“…3 and 4 show the visible micro-Raman and resonant Raman spectra of the nanorods grown under different conditions. The visible Raman spectra from the samples show phonon peaks of ZnO at 438 and 332 cm À1 , and are assigned as E 2 high and E 2 high -E 2 low modes of hexagonal ZnO, respectively [6][7][8][9]. The Raman peaks at 576.7, 418, and 379.5 cm À1 marked with asterisks in the spectra are the phonon modes appearing from the sapphire substrates.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…And we also suggested that the nanopores of anodic aluminum oxide template may play an important role in controlling the local concentration which leads to an inhomogeneous concentration distribution and may affect the shape development. [14][15][16] But, as Figure 2b-d revealed, a transition layer has been clearly found and no changed with extending duration time, which was inconsistent with our foregone suggestion.…”
contrasting
confidence: 49%
“…In order to avoid the problem, metal catalyst-free growth of the ZnO nanostructures has been also reported by MOCVD, etc. [9][10][11][12][13][14] Along with the growth of high quality nanostructures, in another point of view, the alignment and patterning of the nanostructures are also important issues in order to expand the potential applications into nano-device technology. Several methods have been extensively studied to architecturally control both the shape and the selective growth of the ZnO nanostructures on substrates.…”
Section: Introductionmentioning
confidence: 99%